Tropical fruits - Paull, Robert E.; Duarte, Odilo (Crop production science in horticulture series, 2011)
Covers major tropical fruits such as avocado, litchi, mango, papaya and pineapple. This book describes the tropics and their soils, deals with key issues such as tree management and postharvest handling, and includes best handling practices and food safety issues and the way to address these issues in marketing